Efektifitas Implementasi E-Tilang Kendaraan Bermotor Dalam Rangka Tertib Berlalu Lintas Pada Korps Lalu Lintas Polri - Chusminah Chusminah; R. Ati Haryati; Desi Kristiani (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Traffic violations that often occur on the highway make the Korps Lalu Lintas Polri in the current era of globalization more innovating in terms of the enforcement traffic violations in order to make it easier for the public to know the procedure of electronic-based Ticketed recently launched by Korps Lalu Lintas Polri. The methods used for research there in the end this is a method of observation, interview methods, and methods of documentation. This study aims to analyze effectivety of e-ticketed violations implementation in Korps Lalu Lintas Polri. Based on the results of the research done, the implementation of Electronic Ticketed or e-Ticketed applied by Korps Lalu Lintas Polri that is started from the enforcement traffic violations to offenders, input data in the application of e-Ticketed by Korps Lalu Lintas Polri members, followed by the payment of a fine of maximum committed by offenders to the Bank, data offenders sent to the Court to accept the Statute of judges, so that the Prosecutor can execute the ruling of speeding tickets. After that, violators will receive a notification and the remaining funds ticketed verdict speeding tickets that can be taken back through these exhibits can be taken back. Application of the maximum fines of procedure e-Ticketed is expected to reduce traffic violations increasing until recently.  Keywords: Effectivity, Implementation, Speeding Ticket